Describing Function Analysis of Sustained Oscillations in Grid-Tied Voltage-Source Converter With Double Saturation Limiters - Huang, Yifan; Ma, Rui; Zhan, Meng; Cao, Kan; Ye, Chang (Frontiers in Energy Research, 2022)
Recently, with the fast development of renewable energy, various power-electronic-based devices have been widely incorporated in power systems, and controller saturation limiters have been broadly utilized, such as in voltage-source converter. It has been recognized that these saturation limiters make sustained oscillations be possible. To study the impact of saturation limiters, by considering the dynamical response of double saturation limiters in both the d-axis and q-axis of the alternating current control, this paper establishes single-input-single-output models for two novel phenomena including the double-clipped oscillation and single-clipped oscillation, based on the describing function. Then the describing function-based Nyquist criterion is used to obtain the amplitude and frequency of the sustained oscillations. The model accuracy is verified by the electromagnetic transient simulation, and the influences of control parameters are extensively studied. All these findings clearly show that the saturation limiters play an active role in sustained oscillations in power-electronic-based power systems.